2010
DOI: 10.1128/iai.00767-09
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Mucosal Innate and Adaptive Immune Responses and Resolution of Diarrheal Pathogen Infections

Abstract: The identification of immune response mechanisms that contribute to the control of diarrheal disease in developing countries remains an important priority. We addressed the role of fecal chemokines and cytokines in the resolution of diarrheal Escherichia coli and Giardia lamblia infections. Stools collected from 127 Mexican children 5 to 15 months of age enrolled in a randomized, double-blind, placebo-controlled, vitamin A supplementation trial were screened for enteropathogenic Escherichia coli (EPEC), entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 52 publications
(52 reference statements)
4
51
0
3
Order By: Relevance
“…The immune response at these time points is characterized by a predominance of B220 + cells in the lamina propria, elevated Il4 and Il5 mRNA, and intraepithelial eosinophils, consistent with a Th2-biased response. Similarly, markers of Th2 responses have been documented in human infections, including eosinophilic infiltrates in approximately one-third of jejunal biopsies from children (40), elevated IL-4 and IL-5 in stools of children who fail to clear Giardia (41), and elevated serum IL-13 following acute infection in adults (45). The mechanisms driving this response are poorly understood, and the clinical studies did not exclude the presence of coinfecting helminths, which is associated with both mucosal eosinophils and susceptibility to G. lamblia (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune response at these time points is characterized by a predominance of B220 + cells in the lamina propria, elevated Il4 and Il5 mRNA, and intraepithelial eosinophils, consistent with a Th2-biased response. Similarly, markers of Th2 responses have been documented in human infections, including eosinophilic infiltrates in approximately one-third of jejunal biopsies from children (40), elevated IL-4 and IL-5 in stools of children who fail to clear Giardia (41), and elevated serum IL-13 following acute infection in adults (45). The mechanisms driving this response are poorly understood, and the clinical studies did not exclude the presence of coinfecting helminths, which is associated with both mucosal eosinophils and susceptibility to G. lamblia (46).…”
Section: Discussionmentioning
confidence: 99%
“…In longitudinal studies of children in Mexico, stool cytokine analysis showed that children who failed to clear Giaridia had increased IL-4, IL-5, MCP1, and IFN-γ, and decreased IL-8 (41). Observing that eosinophils were increased, we proceeded to investigate mRNA cytokine profiles in matched mouse duodenal tissues ( Figure 5, A-I).…”
Section: L-n)mentioning
confidence: 99%
“…Zinc may delay the development of a protective Th2 response during this critical period. Elevated fecal Th2 cytokine concentrations among vitamin A supplemented children in this same community are associated with reduced lengths of G. intestinalis infection (Long KZ et al, 2010;Long KZ et al, 2011).…”
Section: Histolytica/edispar Infection Duration Is Congruent With Stmentioning
confidence: 86%
“…In severe cases of giardiasis, during infection Giardia trophozoites attach to the epithelium of the proximal small bowel aided by their ventral adhesive discs, evade host defenses possibly by undergoing genetic variation (12), and produce local alterations of villus structure and cellular apoptosis. The most devastating effects of Giardia infection are related to damage of the absorptive small bowel mucosa, together with abnormal intestinal immunity that favors chronic infection (13,14). While there is little evidence that preexistent malnutrition in young children makes them more susceptible to Giardia infection, once they are infected, persistent symptoms and health consequences are more likely to develop (15).…”
Section: Discussionmentioning
confidence: 99%